Perbandingan Perilaku Struktur Beton Dengan Tulangan Baja Dan Struktur Beton dengan Glass Fiber Reinforced Polymer (GFRP) - Arief, Naufal; Ridwan, Ridwan; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Fiber Reinforced Polymer (FRP) was a composite material that has a tensile strength of 7 to 10 times the tensile strength of steel. FRP made from three types of composite materials, namely Carbon, Glass and Aramid. In this research, Glass-FRP material is used. FRP material tensile test results show a linear stress-strain relationship. Theoretically this indicates that FRP material was brittle, it was considered necessary to study the behavior of the structure using FRP material. This study aims to compare the behavior of steel reinforced concrete portal structures with FRP reinforced concrete portal structures in receiving earthquake loads. The analytical method used was the time history analysis used the 2009 Pariaman earthquake record, and the FRP reinforcement calculated refers to ACI 440-1R-2015. The amount of reinforcement needed in a concrete beam with GFRP reinforcement is the same as the reinforcement of a concrete structure beam with conventional steel reinforcement. That is because the amount of reduction required by ACI 440.1R-2015 for the calculation of GFRP reinforcement. The value of relative displacement in the structural model with GFRP reinforcement was 7.34% greater than the structural model with steel reinforcement. Velocity and acceleration values were 65% and 52.87%, respectively, which indicates that vibrations in structures with GFRP reinforcement during an earthquake were less pronounced than structures with steel reinforcement.Keywords: Reinforcement FRP, Convensional Steel Reinforcement, Reinforcement GFRP